Breaking the silence: Listening to interviewers when considering sources of non-sampling errors in household survey research in South Africa. - Kriel, Antoinette; Risenga, Arthur (South African Review of Sociology, 2014)
Interviewers make an important contribution to the quality of data collected through interviewer-administered questionnaires. However, once this data has been collected not much attention is paid to non-sampling errors and the data is accepted at face value. Failure to adequately understand and address these issues can severely limit the usefulness of the research outcomes. The purpose of this paper is to explore ambiguous contexts in household survey data production in South Africa, and to understand the origins of the ambiguities and how interviewer decisions could affect data collection within these contexts. For this purpose the South African Household Financial Wellness Survey conducted by the Personal Finance Research Unit at Unisa in 2011 was used as a case study.